A Lead Market Approach Towards the Emergence and Diffusion of Coal-fired Power Plant Technology - Klaus Rennings; Wilko Smidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Today, more than 70% of the world?s total electricity production is supplied by power plants using conventional fossil fuels. Coal accounts for more than half of the fossil fuel combustion in electricity plants. Future mega trends give reason to believe that electricity demand will double until 2030. The abundance of coal reserves in many countries and increasing fuel prices for gas and oil against the background of a growing need to provide sufficient, secure and affordable energy make coal an attractive option in worldwide electricity production. Against this background, the aim of this paper is to analyse why clean coal technologies in some countries diffuse faster and to a greater extent than in other nations. The paper applies the lead market concept. Lead markets are markets that adopt an innovation before it is adopted by most other countries and therefore lead the global diffusion of the innovation. The most important technological trajectory for coal power plants is the pulverised coal-fired steam cycle (PC) which is the basis for all other coal combustion technologies. Modern PC technology is well developed and accounts for over 90% of coal-fired capacity worldwide. Therefore it will be taken as a reference technology, with SC (Supercritical) coal-fired power generation technologies being selected as an innovative technology within this trajectory. As for the diffusion of SC, the paper concentrates on Germany, USA, China and Japan. The analysis shows that the typical lead market pattern applies only to a limited extent. In the 1960s and 1970s, the USA has established a lead market for SC technology. In the meanwhile, Japan has surpassed the United States, although it started out as typical lag market. After analysing the technology diffusion in the four countries, one central question evolves: Can we determine a lead market for coal-fired power plant technology today? The discussion of lead market factors shows that currently no clear lead market exists for coal-fired power plant technology. Although the United States still has comparative advantages in terms of prices, demand and market structure, Japan has caught up in terms of transfer advantage and Germany in terms of regulation. In the near future, demand advantages will switch to China. This supports also the hypothesis that - apart from the demand-oriented lead market model - push factors such as R&D activity play a strong role as well. The transfer advantage of Japan stems mainly from its intensive R&D activities. Thus it can be concluded that a mix of push and pull policies is necessary in order to establish a lead market position.
Keywords: L50; Q50; O33; 330; Lead Markets; Coal Power plants; Energy Technology; Energy Policy